Recrutement et sélection du personnel - Malo, François Bernard (Relations industrielles / Industrial Relations, 2009)
The article reviews the book, "Recrutement et sélection du personnel," by Anne Bourhis.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les stratégies des ressources humaines - Malo, François Bernard (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "Les strategies des ressources humaines," 3rd edition, by Bernard Gazier.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resources; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Workforce Scorecard: Managing Human Capital to Execute Strategy - Malo, François Bernard (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "The Workforce Scorecard: Managing Human Capital to Execute Strategy," by Mark A. Huselid, Brian E. Becker and Richard W. Beatty.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z